Enhancing Geometric Shape Recognition Ability in Group A Children Through Geometric Satay Educational Toy at TK ABA - Hasana, Tri Sofia; Prayogo, Basuki Hadi; Suwargono, Trio (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2025)
This study intents to improve the ability to recognize geometric shapes in 15 Group A children at TK Aisyiyah Bustanul Athfal using an educational toy (APE) called “Geometric Fruit Satay.” The main issue in this study is the low level of children’s understanding of geometric shapes, as indicated by a pre-cycle average score of 1.50. This research is a Classroom Action Research (CAR) using the Elliot model (1991), conducted over two cycles. Data collection techniques included observation, documentation, and informal interviews, with descriptive quantitative data analysis. The results showed an increase in the average score of geometric shape recognition ability from 1.50 (pre-cycle) to 2.35 (Cycle I), and a significant increase to 3.20 in Cycle II. The highest improvement was in the indicator of classifying shapes by type, which increased by 1.93 points. These findings indicate that using concrete game-based APEs such as Geometric Fruit Satay effectively stimulates conceptual understanding through active motor and exploratory activities in children.